Traditional Market Development Strategy in Langsa City - Rosmeini Banurea; Dela Pramita; Dara Balqis (PT FORMOSA CENDEKIA GLOBAL, 2022)
The purpose of this research is to formulate a strategy for the development of the Langsa City Traditional Market. The analytical method used is Soar Analysis. The population in this research is all people who are involved in the traditional market area of ​​Langsa City. The sample in this study totaled 13 people consisting of buyers, traders and local government. Based on the results of the study, it was found that the Langsa City Traditional Market Will Still Be the Choice of the Langsa City People in Fulfilling Their Daily Life Needs. This can be seen from the Opportunities and Strengths of the Langsa City Traditional Market. The Opportunities and Strengths of the Traditional Markets of Langsa City Show That the Traditional Markets of Langsa City In The Future Can Develop Even Better. The most suitable strategy for dealing with the problem of the Langsa City Traditional Market is to carry out physical development of the Langsa traditional market.